Analisis Efisiensi Pemasaran Kopi Robusta Di Kabupaten Banjar - Mahyudi, Fitri; Husinsyah (Chlorophyl, 2023)
Robusta coffee is a commodity in Banjar Regency. The existence of a gap in coffee prices at the producer and consumer level by 77,04 percent is suspected that a large number of marketing institutions are involved, resulting in high marketing costs. This has led to allegations of unequal pay among marketing institutions. It has an impact on the level of coffee marketing efficiency in the Karang Intan District. Therefore, this study aimed to analyze the Robusta coffee marketing system that is formed, based on the institutions involved, and analyze the Robusta coffee marketing efficiency in Karang Intan District. Research data was obtained from observations, interviews using questionnaires, and supporting data from relevant agencies. The results showed that four marketing channels carried out each marketing function. Based on quantitative calculations, channel I is the most efficient channel with a margin of Rp 7.200 per kg and a farmer’s share of 77,84 percent. Efforts to overcome coffee marketing inefficiencies in Karang Intan District, Banjar Regency through the optimal implementation of marketing functions at each marketing agency, efforts to improve post-harvest quality and sales of coffee products that have been processed into sangria coffee or powder to encourage increased selling prices and farmers' income.